Modification of maladaptive memories during sleep and wakefulness: an interdisciplinary perspective - Bonilla, Matías; Jorge, Camila Isabel; Moyano, Malen Daiana; Forcato, Cecilia (Facultad de Psicología (Universidad Nacional de La Plata, Argentina), 2020)
Consolidated memories can return to a labile state after a reminder presentation (cue associated to the initial learning) followed by a re-stabilization process known as reconsolidation. Furthermore, sleep has an active role in the formation and modification of memories, as well as in decreasing the emotional tone of the experiences. During sleep, new memories are reactivated, reinforced and integrated into pre-existing networks. Within the therapeutic context, old memories can be retrieved according to the subject's needs, and this could be triggering repeated labilization/re-stabilization processes, perhaps without being aware of it. . In this review we discuss the neuroscientific advances regarding memory reactivation and modification during sleep and wakefulness, as well as the latest approaches in psychotherapeutic therapies for anxiety disorders, with the aim of thinking about a more interdisciplinary practice.